Association Between Phase Angle and Sarcopenia in Patients Undergoing Peritoneal Dialysis - Do, Jun Young; Kim, A. Young; Kang, Seok Hui (Frontiers in Nutrition, 2021)
Introduction: There is limited data on the association between phase angle (PhA) and sarcopenia using both muscle strength and muscle mass in peritoneal dialysis (PD) patients. We aimed to evaluate the association between PhA and sarcopenia in PD patients. Methods: We enrolled prevalent PD patients (n = 200). The patients were divided into tertiles based on the PhA level: low (n = 66, 1.9–4.0°), middle (n = 68, 4.1–4.9°), and high tertiles (n = 66, 5.0–8.0°). PhA was measured using bioimpedance analysis. The handgrip strength (HGS) was measured in all patients. Body compositions were measured using dual energy X-ray absorptiometry (DXA). Results: HGS and/or lean mass indices showed poorer trends in the low tertile than in the other tertiles. PhA was positively associated with HGS and/or muscle mass index. Multivariate analyses showed that the patients in the low tertile had an odds ratio of 9.8 (p = 0.001) and 52.79 (p < 0.001) for developing sarcopenia compared to those in the middle and high tertiles, respectively. Subgroup analyses using these variables yielded results similar to those from the total cohort. Conclusion: The present study demonstrated that PhA is independently associated with muscle mass using DXA, strength, and sarcopenia in PD patients. These results suggest that PhA can be used as a valuable and simple predictor for identifying PD patients at risk of sarcopenia.